Management of Refractory Hypoxemia During Venovenous Extracorporeal Membrane Oxygenation for ARDS. Issue 3 (May 2015) - Montisci, Andrea; Maj, Giulia; Zangrillo, Alberto; Winterton, Dario; Pappalardo, Federico
<x xml:space="preserve">Abstract</x> Venovenous extracorporeal membrane oxygenation (VV ECMO) in acute respiratory distress syndrome (ARDS) is currently a widely used therapeutic strategy. However, patients are often still hypoxemic despite complete ECMO support. The major determinants of peripheral oxygen saturation (SpO2) during VV ECMO are pump flow, degree of recirculation, patient's systemic venous return and its oxygen saturation, hemoglobin concentration and residual lung function. Current guidelines state that the support can be considered adequate when the patient's SpO2 is equal or greater than 80%, but a possible objection could be that such a value of O2-tension may be too low and may worsen the patient's prognosis. Moving from the pathophysiology of hypoxemia during VV ECMO, this review focuses on recirculation of blood and on the possible strategies to minimize it, on the pharmacologic modulation of intrapulmonary shunt and on the questions related to management of ECMO flow and the risks and benefits of permissive hypoxemic states. Transfusional strategy during VV ECMO, administration of neuromuscular blocking agents and sedatives, therapeutic hypothermia, and prone positioning is also reviewed. The potential advantages of β-blockers are discussed. Finally, transition from VV ECMO to venoarterial ECMO (VA ECMO) or a hybrid configuration is also examined.